Fatty acids and triacylglycerols in the seed oils of Saudi Arabian date (Phoenix dactylifera L.) palms. (26th October 2019) - Lieb, Veronika M.; Kleiber, Caroline; Metwali, Ehab M.R.; Kadasa, Naif M.S.; Almaghrabi, Omar A.; Steingass, Christof B.; Carle, Reinhold
Summary: Total lipids, fatty acids and triacylglycerols in seeds of the four Saudi Arabian date cultivars 'Anbra', 'Megadwel', 'Sacai' and 'Sfwai' were analysed. Total lipid contents ranged between 7.3 and 8.6%. Oleic, lauric and myristic acid represented the most abundant fatty acids in date seed oil. HPLC‐DAD‐ESI‐MS n analysis enabled the identification of 40 triacylglycerols with equivalent carbon number (ECN) 36–54, of which 17 were detected for the first time. Triacylglycerols mainly comprised LaOL, LaLaL, LaML, MML/LaPL and LaOO. 'Anbra' oil was characterised by highest proportions of saturated fatty acids and triacylglycerols with ECN 36 and 48–54. Unsaturated fatty acids prevailed in the three remaining varieties. Elevated proportions of triacylglycerols with medium ECNs were found in 'Megadwel' and 'Sfwai' oils. Aside from highest total lipid contents, 'Sacai' seeds predominantly contained triacylglycerols with low ECNs. Multivariate statistical analyses elucidated varietal influences on the fatty acid and triacylglycerol composition of date seed oil. Abstract : Characterisation of fatty acids and triacylglycerols in seed oils derived from four Saudi Arabian date cultivars ( Phoenix dactylifera L. ) applicable in the food and cosmetic industry.